دراسة مقاومة العينات البيتونية في منشآت منفذة وتحقيقها لمبدأ التصميم بالطريقة الحدية - الجنزير, سهيل (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر المقاومة على الضغط من أهم خواص البيتون، وترتبط هذه المقاومة بشكل كبير بالبنية المجهرية للبيتون التي تؤثر في الخواص الأخرى كالمرونة. إن الغاية من هذه الدراسة هي الإجابة على السؤال: هل المقاومات الفعلية للعينات البيتونية للمشاريع المدروسة في هذا البحث تحقق مبدأ التصميم وفق الطريقة الحدية؟ وذلك من خلال دراسة نتائج كسر العينات البيتونية الواردة إلى مخبر تجريب المواد في كلية الهندسة المدنية بجامعة حلب خلال عامي 2003 و2004. أظهرت هذه الدراسة أن نسبة المشاريع التي لم تحقق قيمة المقاومة المميزة الأسطوانية والتي اعتمدت أساساً للدراسة خلال عامي 2003 و2004 تتجاوز40 %، كما أن نسبة المشاريع التي لم تتجاوز مقاومتها المميزة الأسطوانية خلال عامي الدراسة تصل إلى حوالي %20. إن نتائج هذه الدراسة تفرض إجراء الدراسات النظرية والتجريبية للحصول على بيتون ذي مقاومة مميزة عالية مع الأخذ بعين الاعتبار ظروف التنفيذ المحلية. Compressive strength is considered one of the main characteristics of concrete. Compressive strength depends on the microscopical structure of the concrete, which affects the other properties such as elasticity. The purpose of this study is to answer the question: Do the actual compressive strengths of concrete samples for projects studied in this research achieve the design principle in the Ultimate Strength Method? This is done based on the results of concrete samples fracture experimented in the Materials Experiment Laboratory at the Faculty of Civil Engineering in Aleppo University for the two years: 2003 and 2004. This study demonstrates that 40% of the projects which were studied did not achieve the average characteristic compressive strength, which is 180 kg/cm^2, and the characteristic compressive strength for 20% of the projects did not exceed 150 kg/cm^2. The results of study require more theoretical and experimental studies to make high characteristic compressive strength concrete.